Avaliação da eficiência na atenção básica à saúde no Brasil e região Nordeste - Silva, Camila Ribeiro da (2017)
This dissertation aimed to identify the factors that inﬂuence the technical efﬁciency in the application of resources destined to primary care in Brazil, in the northeastern region and in the state of Paraíba. For this, the inﬂated beta regression model was used, since the response variable presents asymmetry and is restricted to the range (0,1]. The sample used was from secondary data obtained from public domain sources. After the descriptive analysis of the data we veriﬁed that, of the total of municipalities of the sample (3.409), only 15.6% are considered fully efﬁcient in the application of the resources destined to the basic attention. The northern and northeastern regions presented, in general, a greater proportion of children under 5 years of age when compared to the other regions. It was observed that only 0.12 % of the municipalities observed have complete coverage regarding basic sanitation services, being Espírito Santo do Pinhal, Ituverava, Junqueirópolis and São José dos Campos, all located in the state of São Paulo. After adjusting the regression models, it was veriﬁed that, in the model that considers data for Brazil, the Firjan index of municipal development in health, the municipal population and the percentage of families with basic sanitation services exert a positive effect on efﬁciency average of the municipality. While in the Northeast, the variables per capita expenditure on basic care, municipal population and Firjan index of development in education exert a positive effect on the average efﬁciency of basic care. For the model with data from Paraíba, the variables number of visits per establishment and average number of doctors per establishment of primary care negatively inﬂuence the average efﬁciency of the municipality.